AI-Driven Human Resource Management and Its Impact on Employee Performance: The Mediating Role of Employee Trust in Artificial Intelligence - Nurdiana Mulyatini; Yusup Iskandar; Mulia Sosiady; Elvie Maria; Peni Cahyati (Dinasti Publisher, 2026)
The rapid adoption of artificial intelligence (AI) in human resource management (HRM) has transformed organizational practices in performance management, recruitment, and workforce analytics. AI-driven HRM enables data-based decision-making, predictive performance evaluation, and automated talent management processes. However, the effectiveness of AI implementation depends on both technological capability and employee trust in artificial intelligence. This study aims to examine the effect of AI-Driven Human Resource Management on Employee Performance, with Employee Trust in Artificial Intelligence as a mediating variable. This study employs a quantitative explanatory survey design. Data were collected from employees in organizations implementing AI-based HR systems. The sample size was determined based on SEM requirements. Data analysis was conducted using SEM to test direct and indirect relationships among variables. The results indicate that AI-Driven HRM has a positive and significant effect on Employee Trust in Artificial Intelligence. Employee Trust in Artificial Intelligence significantly influences Employee Performance. AI-Driven HRM also has a direct positive effect on Employee Performance. Furthermore, Employee Trust in Artificial Intelligence partially mediates the relationship between AI-Driven HRM and Employee Performance. These findings suggest that the successful implementation of AI in HRM requires not only technological infrastructure but also the development of employee trust to enhance performance outcomes. This study contributes to the strategic human resource management literature by integrating AI capability and psychological trust mechanisms into a unified performance model. Practically, organizations are advised to ensure transparency, fairness, and ethical AI implementation to strengthen employee trust and maximize performance benefits.